2018
DOI: 10.1021/acs.joc.8b01676
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Formation Mechanism of 1,3,4-Oxadiazole-2(3H)-ones from Hydrazonyl Chloride and Carbon Dioxide

Abstract: The reaction mechanism for the synthesis of 1,3,4-oxadiazole-2­(3H)-ones from hydrazonyl chloride and CO2 in the presence of CsF/18-crown-6 and toluene, is revisited via density functional theory computations. Although this reaction was earlier classified as a 1,3-dipolar cycloaddition, we found some competing pathways involved therein. The mechanisms including the (F–CO2)− anion and the nitrile imine intermediate are some options. The dimerization of nitrile imine is another competing mechanism in this reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The rate-determining step is the final five-membered ring closure. However, authors affirmed that increasing the concentration and the temperature the concerted pathway becomes more likely [185].…”
Section: Scheme 13mentioning
confidence: 99%
“…The rate-determining step is the final five-membered ring closure. However, authors affirmed that increasing the concentration and the temperature the concerted pathway becomes more likely [185].…”
Section: Scheme 13mentioning
confidence: 99%
“…[6] In addition, the cycloaddition reactivity of allenes can be broadened to heteroallenes, such as ketenimine( CCN), [7] ketene( CCO), [8] carbodiimide (NCN), [9] isocyanate (NCO), [10] and even to carbon dioxide (OCO). [11] In contrast,s trained allenes, that is, cyclica llenes, have receivedless attention in the field likely duet ot heir lower kinetic stabilities. [12] Nevertheless, experimental studies have shown that strained allenes can be formed in situ and trapped instantaneously by either dienes or 1,3-dipoles.…”
Section: Introductionmentioning
confidence: 99%
“… The use of simple Lewis bases (e.g., F – ) as catalysts for the activation of small molecules, which allows for efficient transformations under mild conditions, is of high interest . Merino and co-workers previously investigated this reaction computationally and provided evidence for an operative mechanism based on the analysis of a number of possibly competing potential energy surfaces; however, they did not comment on the origin of the catalytic effect of the F – Lewis base . Lu and co-workers experimentally showed that a base alone does not efficiently facilitate the cycloaddition reaction, so that F – is playing another role, presumably as a catalyst .…”
mentioning
confidence: 97%
“…This intermediate then undergoes intramolecular ring formation, through III-TS2 with a barrier of 14.3 kcal mol –1 , to then form product 3 and regain the Lewis base F – . We have also computed pathway III with the corresponding Cl – adduct of 1 , which is a similar intermediate to that proposed by Merino and co-workers, and we found that F – adduct 2 follows a lower energy pathway in the reaction with CO 2 (see Supporting Information, Schemes S1–S3 and Figure S1).…”
mentioning
confidence: 99%